2021
DOI: 10.18203/2319-2003.ijbcp20212083
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of knowledge, attitude and perception about adverse drug reactions and pharmacovigilance among intern doctors in a medical college teaching hospital of Sangli

Abstract: Background: Underreporting of various adverse drug reactions (ADRs) by consultants is a common incurable problem. National pharmacovigilance program is one of the ongoing programs to monitor the adverse drug reactions & reporting at the earliest to the nearby AMCs. As medical interns are budding doctors, the focus of this study was to evaluate the knowledge, attitude and perception about ADRs and pharmacovigilance in them.Methods: A cross section questionnaire-based study was conducted after approval by ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…Also, a study conducted in India identified shallow awareness of pharmacovigilance programs among doctors [16,17]. Intern doctors, too, had lower knowledge of pharmacovigilance compared to the findings in this study, as reported by [10,11,18]. In this study, most participants believe that newly introduced drugs should be reported.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Also, a study conducted in India identified shallow awareness of pharmacovigilance programs among doctors [16,17]. Intern doctors, too, had lower knowledge of pharmacovigilance compared to the findings in this study, as reported by [10,11,18]. In this study, most participants believe that newly introduced drugs should be reported.…”
Section: Discussioncontrasting
confidence: 48%
“…As a result, pharmacovigilance practices, including identifying and reporting ADRs, are now anticipated by intern pharmacists in training. Pharmacists and interns are easily accessible, work for long hours, and interact with numerous patients and thus are in an ideal position to undertake pharmacovigilance and identify and report adverse drug reactions (ADRs) [10]. Participation in pharmacovigilance exercises mostly depends on the pharmacist intern's understanding of what PV includes and the necessity of engaging in such activities.…”
Section: Introductionmentioning
confidence: 99%